Keterampilan Pemecahan Masalah MatematisPada Peserta Didik Kelas V Sekolah Dasar - Anesa Surya, Meti Widiawati, Siti Istiyati (Jurnal Pendidikan Dasar, 2019)
The purpose of this research is to analyzing mathematical problem solving skills in fifth grade elementary school students. The research is descriptive research, using a qualitative approach. The technique of collecting data uses tests. The research subjects were fifth grade students of SD Negeri Danukusuman in the 2018/2019 academic year. The data analysis technique used is descriptive and content analysis. The results of research indicate that mathematical problem solving skills in the solid figure of fifth grade elementary school students were still low. In the indicators of problem comprehension skills, the percentage of skilled students is 62.5%. On the indicator of skills for problem solving, the percentage of skilled students is 21.88%. On the skill indicator carrying out the problem solving procedure, the percentage of skilled students is 0.09%. On the skill indicator, checking and drawing conclusions, the percentage of skilled students is 0.06%. The results of this research were preliminary studies for developing innovative learning models to improve problem solving skills.Keywords: problem solving skills, mathematics learning, solid figure, students, elementary school